Pengaruh Pupuk Hayati Cair BRE4 dan Pupuk Organik Terhadap Keragaman Nematoda Tanah Pada Lahan Kopi Arabika: Pengaruh Pupuk Hayati Cair BRE4 dan Pupuk Organik Terhadap Keragaman Nematoda Tanah Pada Lahan Kopi Arabika - Iis Nur Asyiah; Mudakir Imam; Pradana Ankardiansyah Pandu; Budiman Aris; Nugroho Dwi; Nordiana Laeli (Politeknik Negeri Lampung., 2024)
This research aims to determine the influence of liquid biofertilizer BRE4 and organic fertilizer on soil nematode diversity in Arabica coffee plantations. The study was conducted in smallholder Arabica coffee farms in the Ijen Bondowoso region, Indonesia. The research utilized a Randomized Complete Block Design with the following treatments: P1= 30 ml of liquid biofertilizer BRE4 per ton of manure, P2= 60 ml of liquid biofertilizer BRE4 per ton of manure, P3= 90 ml of liquid biofertilizer BRE4 per ton of manure, P4= 120 ml of liquid biofertilizer BRE4 per ton of manure, K- = Without liquid biofertilizer and manure, K+1= 60 ml of liquid biofertilizer, and K+2= 5L of manure without liquid biofertilizer. The results showed that the P4 treatment reduced the population of parasitic nematodes and increased the diversity of free-living nematodes better than other treatments. A total of 18 genera of soil nematodes were identified, with the bacterial-feeding nematode genus (bacteriovore) being the most abundant compared to other trophic groups. The application of BRE4 and manure improved the soil ecosystem based on the nematode diversity level.